Development of optogenetics in the world and in Russia: leading researchers and technological drivers - A. V. Komarova; M. V. Galyamova; O. V. Cherchenko (Ekonomika Nauki)
The article presents a scientometrical and patent analysis of a new perspective scientific area called «optogenetics» with the usage of bibliometric data bases Web of Science and Scopus, as well as other analytical tools such as Essential Science Indicators SM (ESI), SciVal Spotlight, Orbit. There is identified a currently formed structure of scientific communities — drivers of development in this area. There is suggested a plan of actions directed on development of optogenetics in Russia with consideration of country opportunities.